Obesity and dyslipidemia in patients with psoriasis: A case–control study. Issue 31 (August 2019) - Miao, Chaoyang; Li, Jing; Li, Ying; Zhang, Xiaoyan
Abstract : Abstract: The aim of this study was to conduct a more comprehensive analysis of the association between psoriasis and abnormal lipid metabolism. The case–control study included 222 psoriatic patients and 445 non-psoriatic control patients matched for age and gender. Clinical parameters included age, gender, and body mass index (BMI). Serum lipid levels were recorded and included cholesterol (CHO), triglycerides (TG), low-density lipoprotein (LDL), high density lipoprotein (HDL), phospholipids (PLIP), free fatty acids (FFA), lipoprotein (a) [Lp(a)], and apolipoproteins (apoA1, apoB, and apoE). Statistical analysis was carried out through the IBM Statistical Package for the Social Studies version 23.0. Compared with controls, levels of BMI and the prevalence of obesity were significantly higher in psoriatic patients. The results revealed that when compared to controls, significant elevation of serum TG ( P <.001) and Lp(a) ( P = .022) was observed. Levels of HDL ( P <.001) and apoA1 ( P <.001) were significantly lower in psoriatic patients. There was no significant difference in CHO ( P = .367), LDL ( P = .400), apoB ( P = .294), apoE ( P = .05), PLIP ( P = .931) and FFA ( P = .554) between patients and controls. The levels of CHO, TG, PLIP, FFA, and apoE were positively correlated with BMI level. Dyslipidemia was more common in psoriatic patients, compared with non-psoriatic controls.